Determination of secondary and tertiary structures of cervical cancer lncRNA diagnostic and siRNA therapeutic biomarkers - Arli Aditya Parikesit; Didik Huswo Utomo; Nihayatul Karimah (Indonesian Journal of Biotechnology, 2018)
Cervical cancer is one of the primary causes of mortality in women due to human papilloma virus (HPV) infection. The fingerprint of an HPV infection could be detected using a long non-coding RNA (lncRNA) biomarker, enabling it to be utilized in molecular diagnostics. The primary structure or sequences of RNA should be annotated within conventional bioinformatics tools. Therefore, this study aimed to determine the fine-grained 2D and 3D structures of lncRNA PVT1 and its respective siRNA inhibitors. lncRNA PVT1 sequences from Homo sapiens, Mus musculus, and Rattus norvegicus were retrieved from Genbank (NCBI). Prediction of the 2D structure and analysis of the interactions of the lncRNA and siRNA were performed using the Vienna RNA package. The 3D structure of the RNA was computed using the SimRNA and ModeRNA software programs. The results showed that lncRNA PVT1 from H. sapiens and M. musculus had a conserved region. However, the lncRNA from both H. sapiens and M. musculus showed a low conserved region, and the 2D structure could not be determined; thus, the annotation and 2D model focused only on H. sapiens. Both of their lncRNA PVT1 also had a short half-life in the cell. Based on the 3D modeling pipeline, the 3D model of lncRNA PVT1 showed the stability and possible function as molecules, while the PVT1 siRNA-lncRNA interaction analysis revealed that the molecules could bind well. Based on these findings, the structures of both lncRNA PVT1 and its siRNA have the potential to be utilized as biomarkers.